Abstracts 2018
DOI: 10.1136/injuryprevention-2018-safety.429
|View full text |Cite
|
Sign up to set email alerts
|

PW 1921 Ensuring children are being taught the skills for drowning prevention

Abstract: BackgroundReducing child (0–14 years) drowning is a priority of the Australian Water Safety Strategy. Research suggests at least 40% of children cannot achieve national benchmarks of swimming 50 m freestyle; 25 m survival backstroke and treading/sculling water for two minutes by 12 years. School swimming programs vary across Australia; therefore many parents enrol their children in private lessons from a young age.ObjectiveTo provide a situational analysis of what children are learning in private swimming less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…11 Pidgeon and colleagues suggest some migrants to Australia may be at higher risk of drowning based on their time in Australia, country of birth and poor SWS skills. 10 These findings are consistent with other research, suggesting that culturally diverse populations are at higher risk of drowning due to lack of SWS skills, poor risk perception of drowning and overall lower rates of participation in water-based activities. 12,13 These factors present a challenge for drowning prevention practitioners in how to overcome the complexity of drowning prevention for different population groups, from cross-cultural communication, education and participation perspectives.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…11 Pidgeon and colleagues suggest some migrants to Australia may be at higher risk of drowning based on their time in Australia, country of birth and poor SWS skills. 10 These findings are consistent with other research, suggesting that culturally diverse populations are at higher risk of drowning due to lack of SWS skills, poor risk perception of drowning and overall lower rates of participation in water-based activities. 12,13 These factors present a challenge for drowning prevention practitioners in how to overcome the complexity of drowning prevention for different population groups, from cross-cultural communication, education and participation perspectives.…”
Section: Introductionsupporting
confidence: 91%
“…Participant feedback indicated that the programs were too short to learn to swim adequately, despite participants stating they had overcome their fear of water and were now confident to be in the Males are overrepresented in drowning statistics worldwide [1][2][3]10 ; therefore, engaging men in SWS programs is equally important as providing programs for women, in order to reduce drowning. Two participants spoke about their husband's support in learning to swim and willingness to pay for further lessons and, in the future, participating together as a family.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation